Electrostatic gyrokinetic simulations in Wendelstein 7-X geometry: benchmark between the codes stella and GENE. (10th June 2022) - González-Jerez, A.; Xanthopoulos, P.; García-Regaña, J.M.; Calvo, I.; Alcusón, J.; Bañón Navarro, A.; Barnes, M.; Parra, F.I.; Geiger, J.
Abstract : The first experimental campaigns have proven that, due to the optimization of the magnetic configuration with respect to neoclassical transport, the contribution of turbulence is essential to understand and predict the total particle and energy transport in Wendelstein 7-X (W7-X). This has spurred much work on gyrokinetic modelling for the interpretation of the available experimental results and for the preparation of the next campaigns. At the same time, new stellarator gyrokinetic codes have just been or are being developed. It is therefore desirable to have a sufficiently complete, documented and verified set of gyrokinetic simulations in W7-X geometry against which new codes or upgrades of existing codes can be tested and benchmarked. This paper attempts to provide such a set of simulations in the form of a comprehensive benchmark between the recently developed code stella and the well-established code GENE . The benchmark consists of electrostatic gyrokinetic simulations in the W7-X magnetic geometry and includes different flux tubes, linear ion-temperature-gradient (ITG) and trapped-electron-mode stability analyses, computation of linear zonal-flow responses and calculation of ITG-driven heat fluxes.